Movement of Heterorhabditis amazonensis and Steinernema arenarium in search of corn fall armyworm larvae in artificial conditions - Andaló, Vanessa; Santos, Viviane; Moreira, Grazielle F. [UNESP]; Moreira, Camila; Freire, Marcela; Moino Jr., Alcides (Universidade de São Paulo (USP), Escola Superior de Agricultura Luiz de Queiroz (ESALQ), 2012)
Spodoptera frugiperda (Smith, 1797) (Lepidoptera: Noctuidae) is considered to be the main pest of maize crops in Brazil. Entomopathogenic nematodes (EPN) may be used to control this pest and exhibit different, unique abilities to search for their hosts. The movement of EPN in relation to S. frugiperda was evaluated. To test for horizontal movement, a styrofoam enclosure filled with sand was divided into segments, nematodes were placed at the entrance to the enclosure and a larva was placed at the end of each division. The same approach was used to evaluate vertical movement; however, PVC pipes were used in this case. In general, the mortality was inversely proportional to the initial distance between host and nematodes. In the vertical displacement test, both nematodes were able to kill the larvae up to a distance of 25 cm. Therefore, the infective juveniles of H. amazonensis and S. arenarium can search out, infect and kill larvae of S. frugiperda at distances of up to 60 cm and 25 cm of horizontal and vertical displacement, respectively.
Keywords: Spodoptera; biological control; behaviour; strategy; entomopathogenic